1987
DOI: 10.1111/j.1600-0447.1987.tb02805.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between a serotonin and a noradrenaline reuptake blocker in the treatment of depressed outpatients

Abstract: Seventy-five outpatients with major depressive disorder (RDC) were randomly referred to treatment with a dominant serotonin (5-HT) reuptake blocker (zimeldine, 100 mg, b.i.d. n = 40) or a dominant noradrenaline (NA) reuptake blocker (maprotiline, 75 mg, b.i.d. n = 35). Seven patients on each drug were non-responders after up to 4 weeks of treatment and were after a washout week crossed over to the other drug for up to another 8 weeks of treatment. There was a significant and similar improvement after 4 weeks o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

1987
1987
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 14 publications
0
7
0
2
Order By: Relevance
“…1978]. A blood sample was also taken to measure the activity of endogenous 5-HT rcuptake blocker by examining synaptosomal accumulation in rat brain [Nystrom et al, 1986]. A routine EEG examination of about 30 min in length, including hyperventilation, was taken in all of the patients.…”
Section: Methodsmentioning
confidence: 99%
“…1978]. A blood sample was also taken to measure the activity of endogenous 5-HT rcuptake blocker by examining synaptosomal accumulation in rat brain [Nystrom et al, 1986]. A routine EEG examination of about 30 min in length, including hyperventilation, was taken in all of the patients.…”
Section: Methodsmentioning
confidence: 99%
“…For example, Ross and Aberg-Wistedt (1983) reported that the accumulation rate of 14C-serotonin in rat hypothalamic synaptosomes, when they were incubated in the plasma of depressed patients, was decreased for up to 2 weeks after zimeldine withdrawal. Nystrom and Hallstrom (1987) cautioned readers about their own results of depressed patients responding selectively to either zimeldine or to the noradrenergic uptake blocker maprotiline. These drugs had been crossed over in nonresponding patients after only a 1-week drug washout period.…”
Section: Subtypes Of Depression and Singlementioning
confidence: 99%
“…Algunos de estos estudios han incluido variables neurobioquímicas y clínicas que podrían diferenciar entre grupos de pacientes. Así, en un estudio con 65 pacientes hospitalizados con depresión «endógena» se detectaron bajos valores de dos metabolitos de la serotonina (5-HIAA y HVA) en el líquido cefalorraquí-deo en los pacientes que respondieron mejor al ISRS zimelidina, en tanto que los pacientes con valores altos de HMPG (un metabolito de la noradrenalina) en el líquido cefalorraquídeo respondieron mejor a la desipramina [9][10][11][12][13][14] . Se ha sugerido que existen subgrupos de pacientes depresivos con bajos valores centrales de serotonina y pacientes con una tendencia a valores más altos de HVA que responden mejor al ISRN desipramina 9,14,15 , aunque estas observaciones no han sido confirmadas en todos los estudios 16 .…”
Section: Discussionunclassified
“…Aunque no existe un consenso, en diversos estudios comparativos con antidepresivos con efectos predominantemente serotoninérgicos o noradrenérgicos se ha observado que los pacientes con mayor retardo psicomotor no responden bien a fármacos serotoninérgicos, pero sí a fármacos noradrenérgicos 18,19 . Entre estos casos se encuentran pacientes con depresiones melancólicas 20,21 .…”
Section: Figura 2 Puntajes Promedio En La Escala De Impresión Clínicunclassified